Optimizing trees distances in urban streets for insolation mitigation - Bajsanski, Ivana; Stojakovic, Vesna; Milosevic, Dragan (Geographica Pannonica, 2019)
Mitigation of overheating in streets is an important task for urban planners and architects. Urban surfaces in streets, such as footways and façades, can contribute to increase overheating in cities, whereas the trees can help to decrease insolation.In this paper we created an algorithm to determine optimal distance between the trees in a street in order to mitigate façade and footwayinsolation. A parametric study for different street orientations and building geometries was therefore conducted for the hottest wave of the year for the corresponding location. The results show that different trees disposition can mitigate overheating of horizontal and vertical surfaces up to 7%. The algorithmic and parametric approach used in this paper can contribute to more precise urban design guidelines for comfortable streets.
Keywords: street; algorithm; insolation; façade; footways; trees